trans-3-(3,4-Dimethoxyphenyl)-2-(4-nitrophenyl)prop-2-enenitrile - Tan, K.W.; Asiri, A.M.; Khan, S.A.; Ng, S.W. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(17)H(14)N(2)O(4), contains two independent molecules in which the benzene rings are in a trans arrangement with respect to the C=C double bond and the rings are inclined by 4.3 (1) and 22.1 (1)degrees with respect to each other.